International Law on Women's Human Rights on the concerns triggered by the introduction of sex robots into society - Kehlet, Isabella (Department of Public Law, 2022)
In a human-like form and programmed with artificial intelligence, sex robots are becoming increasingly prevalent, also as a result of the restrictions on social interactions caused by the COVID-19 pandemic. Because of their programming, sex robots offer both a physical and psychological dimension for users, thereby raising concerns not usually linked to sex toys. The purpose of this dissertation is to examine whether the international human rights instruments on women's human rights relates to concerns raised by sex robots. The focus is mainly on whether sex robots exacerbate harmful gender stereotypes or can be considered discriminatory against women. Furthermore, it is examined whether a State is obligated to respond to the manufacture, distribution and use of sex robots, even though these activities are carried out by private citizens and entities. By applying a dynamic and teleological approach combined with the Vienna Convention on the Law of Treaties' provisions on treaty interpretation, the relevant treaties, treaty body decisions and soft law are examined to determine whether sex robots are harmful to women and what obligations states have in that regard as a result of private actor activities. Sex robots in their current form portray women in a hypersexualised manner, both with appearance and behaviour. While it is not yet clear whether such portrayal will cause a surge in sexual violence against women, sex robots undoubtedly represent a stereotypical and degrading depiction of women, resulting in adverse effects on women's mental health. According to the Convention on the Elimination of All Forms of Discrimination Against Women and other key human rights treaties, member states have an obligation to modify harmful gender stereotypes and eliminate gender stereotyping and other discriminatory practices towards women. Thus, in relation to sex robots, member states must take appropriate measures, like introducing legislation or policies on sex robots' manufacture, distribution and use. Since restrictive legislation on the use of sex robots may interfere with other fundamental human rights - including the user's right to privacy and health - it is recommended that the measures introduced by states focus on the production of sex robots.